In Africa's forest and jungle: six years among the Yorubas - Stone, Richard Henry (Religion and American culture, 2010)
Introduction -- Along the coast -- Up the Ogun -- In native homes -- The story of Crowther -- In a native caravan -- An African despot -- Our first dwelling -- Some beasts and insects -- Life and language -- Superstitions -- Polygamy -- Some African maladies -- Hunting -- Mental solitude -- Waylaid and captured -- Flight from Ebaddan -- Home again -- Opening battles around Ejahyay -- Worshipping the dead prince -- Leaving the doomed city -- Partial civilization -- Love letters -- A narrow escape -- The human sacrifice -- The stolen child -- Improvements -- Cast among robbers -- The colony of Lagos